The story of Taxol: nature and politics in the pursuit of an anti-cancer drug - Goodman, Jordan; Walsh, Vivien (Cambridge, 2006)
"Taxol is arguably the most celebrated, talked-about and controversial natural product in recent years. It is celebrated because of its efficacy as an anti-cancer drug and because its discovery has provided powerful support for policies concerned with biodiversity; talked about because in the late 1980s and early 1990s the American public was bombarded with news reports and special programmes about the molecule and its host, the Pacific yew; and controversial because during the early 1990s the drug and the tree became embroiled in a number of very sensitive political issues with wide implications for the conduct of public policy. The Story of Taxol tells this story."